High-quality chromosome-level scaffolds of the plant bug Pachypeltis micranthus provide insights into the availability of Mikania micrantha control - Xiafei Wang; Ning Zhao; Liqiong Cai; Naiyong Liu; Jiaying Zhu; Bin Yang (BMC Genomics, 2023)
Abstract Background The plant bug, Pachypeltis micranthus Mu et Liu (Hemiptera: Miridae), is an effective potential biological control agent for Mikania micrantha H.B.K. (Asteraceae; one of the most notorious invasive weeds worldwide). However, limited knowledge about this species hindered its practical application and research. Accordingly, sequencing the genome of this mirid bug holds great significance in controlling M. micrantha. Results Here, 712.72 Mb high-quality chromosome-level scaffolds of P. micranthus were generated, of which 707.51 Mb (99.27%) of assembled sequences were anchored onto 15 chromosome-level scaffolds with contig N50 of 16.84 Mb. The P. micranthus genome had the highest GC content (42.43%) and the second highest proportion of repetitive sequences (375.82 Mb, 52.73%) than the three other mirid bugs (i.e., Apolygus lucorum, Cyrtorhinus lividipennis, and Nesidiocoris tenuis). Phylogenetic analysis showed that P. micranthus clustered with other mirid bugs and diverged from the common ancestor approximately 200 million years ago. Gene family expansion and/or contraction were analyzed, and significantly expanded gene families associated with P. micranthus feeding and adaptation to M. micrantha were manually identified. Compared with the whole body, transcriptome analysis of the salivary gland revealed that most of the upregulated genes were significantly associated with metabolism pathways and peptidase activity, particularly among cysteine peptidase, serine peptidase, and polygalacturonase; this could be one of the reasons for precisely and highly efficient feeding by the oligophagous bug P. micranthus on M. micrantha. Conclusion Collectively, this work provides a crucial chromosome-level scaffolds resource to study the evolutionary adaptation between mirid bug and their host. It is also helpful in searching for novel environment-friendly biological strategies to control M. micrantha.